2018
DOI: 10.1021/acschemneuro.8b00122
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Activities of Dopamine and Its Derivatives toward Metal-Free and Metal-Induced Amyloid-β Aggregation, Oxidative Stress, and Inflammation in Alzheimer’s Disease

Abstract: A catecholamine neurotransmitter, dopamine (DA), is suggested to be linked to the pathology of dementia; however, the involvement of DA and its structural analogues in the pathogenesis of Alzheimer's disease (AD), the most common form of dementia, composed of multiple pathogenic factors has not been clear. Herein, we report that DA and its rationally designed structural derivatives (1-6) based on DA's oxidative transformation are able to modulate multiple pathological elements found in AD [i.e., metal ions, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 71 publications
2
61
0
2
Order By: Relevance
“…Several lines of investigation have shown that dopamine increases cortical excitability by acting through D2-like receptors; these observations support the idea that disruption of the DA system is associated with AD pathophysiology. Currently, dysfunction of DA transmission has been hypothesized as a new player in AD pathophysiology [29]. Consistent with a previous study showing DA neuron loss in the midbrain of 5xFAD mice [25], our study showed that the D2R levels in the striatum of 5xFAD mice were significantly lower than those in the striatum of WT mice.…”
Section: Discussionsupporting
confidence: 92%
“…Several lines of investigation have shown that dopamine increases cortical excitability by acting through D2-like receptors; these observations support the idea that disruption of the DA system is associated with AD pathophysiology. Currently, dysfunction of DA transmission has been hypothesized as a new player in AD pathophysiology [29]. Consistent with a previous study showing DA neuron loss in the midbrain of 5xFAD mice [25], our study showed that the D2R levels in the striatum of 5xFAD mice were significantly lower than those in the striatum of WT mice.…”
Section: Discussionsupporting
confidence: 92%
“…[67] Redox cycling induced by DA on the copper-peptide complexes produces several modifications by DA-derived species of both Ab and PrP peptides,a sw ell as O-atom insertion at His and Met residues. [74,76,78,83] Interestingly,b inding of the peptides to membranes has aq uenching effect on Cu 2+ -promoted DA oxidation, with the exception of Ab,for which the inhibition is only partial. [78] Thequenching effect of the membrane is due to the trapping of Cu + in the sites of the peptides containing asequence with two close methionines, 1 MXXXM 5 -atthe Nterminal of aSyn, and -109 MXHM 112 -inthe fragment following the polar region comprising the octarepeats of PrP peptides.…”
Section: Metal-catalyzed Dopamine Oxidationmentioning
confidence: 99%
“…In the case of αSyn ( K D ≈0.20 μ m ), we found that it decreases Cu 2+ reactivity, but these experiments should be repeated using oligomers instead of monomeric αSyn, in view of the strong promotion of ROS production of αSyn aggregates in the presence of Cu 2+ . Redox cycling induced by DA on the copper–peptide complexes produces several modifications by DA‐derived species of both Aβ and PrP peptides, as well as O‐atom insertion at His and Met residues . Interestingly, binding of the peptides to membranes has a quenching effect on Cu 2+ ‐promoted DA oxidation, with the exception of Aβ, for which the inhibition is only partial .…”
Section: Dopamine Reactivity and Its Metal‐catalyzed Oxidationmentioning
confidence: 99%
“…[74][75][76] Für aSyn (K D % 0.20 mm) [82] fanden wir eine Abnahme der Cu 2+ -Reaktivität, [77] doch sollten diese Experimente mit Oligomeren anstelle von Monomeren von aSyn wiederholt werden, weil aSyn-Aggragate die ROS-Bildung in Gegenwart von Cu 2+ stark begünstigen. [74,76,78,83] Die Bindung der Peptide an Membranen dämpft die Cu 2+ -induzierte DA-Oxidation mit Ausnahme von Ab,b ei dem nur eine partielle Hemmung auftritt. [74,76,78,83] Die Bindung der Peptide an Membranen dämpft die Cu 2+ -induzierte DA-Oxidation mit Ausnahme von Ab,b ei dem nur eine partielle Hemmung auftritt.…”
Section: Methodsunclassified
“…[67] Die Redoxzyklen, die durch DA an den Kupfer-Peptidkomplexen induziert werden, verursachen verschiedene Modifikationen an den Ab-u nd PrP-Peptiden durch Verbindungen, die sich von DA ableiten, außerdem einen O-Atom-Einschub an His-und Met-Resten. [74,76,78,83] Die Bindung der Peptide an Membranen dämpft die Cu 2+ -induzierte DA-Oxidation mit Ausnahme von Ab,b ei dem nur eine partielle Hemmung auftritt. [78] [51,84] Das wichtigste eisenhaltige Protein im Gehirn ist Ferritin (ein aus vielen Untereinheiten bestehendes Eisenspeicherprotein mit H-und L-Ketten), das in besonders großen Mengen in Gliazellen und in geringeren Mengen in dopaminergen Neuronen vorkommt.…”
Section: Angewandte Chemieunclassified